Dielectric functions of thermal electrons polarization of dry atmosphere (up to the heights plane of 12 km) - T.A. Belyi; Yu. Zelenin (Геофизический журнал, 2014)
Spatial dispersion of complex dielectric permeability e = e + ih of a subsystem of thermal electrons and ions of standard dry atmosphere in approximation of average self-consistent electric field based on the right part of sh-Poisson equation is investigated. Verification of constants has been conducted by two different experimental sets of data: a) synchronous ground observations of positive and negative ions; b) vertical profiles of plane sounding of electric field of atmosphere. It has been shown that the values of constants e, obtained according to a) and b) data are within the limits of isotopic ratio for solvated electron e ~  eр ~ 2 × 105 CGSE. Ionic planes are unambiguously bound to the heights of clouds formation. In them e corresponds to dynamic phase transition in the system of coulomb particles. Formulae for valuation of fluctuation dielectric constants in one-mode approximation through the function of generalized productlog logarithm have been presented. Variation of energy functional has been conducted by dielectric constant as a dynamic variable. A series of multiplicative corrections to bolzman probability factor have been obtained. It has been demonstrated that on potential level induction part of virtual charge of displacement currents is present.